Netz.kunst : Jahrbuch '98-'99. - Baker, Rachel; Baumgärten, Tilman; Beck, Stefan; Blank & Jeron; Blase, Christoph; Djordjevic, Valentina; Dorrer, Angela; Friese, Holger; Geelhaar, Jens; Gohlke, Gerrit; Grzinic, Marina; Huber, Hans Dieter; et al. (Nürnberg : Verlag für moderne Kunst, 1999)
Baker, Rachel ; Beck, Stefan ; Blank & Jeron ; Bosma, Josephine ; Dellbrügge & De Moll ; Dorrer, Angela ; Fahrradhalle ; Friese, Holger ; Geelhaar, Jens ; Grubinger, Eva ; Hergueta, Mario ; Huber, Hans Dieter ; Huffman, Kathy Rae ; Idensen, Heiko ; Jahrmann, Margareta ; Jankowski, Christian ; Kuni, Verena ; Lovink, Geert ; Medosch, Armin ; Oldenburg, Helena von ; Rimini, Francesca da ; Shulgin, Alexei ; Sollfrank, Cornelia ; Schütz, Richard ; Weiberg, Kerstin
biografie, bibliografie
Duits
boek